E-153 Transfemoral flow-reversal using walrus balloon-guide catheter for carotid artery stenting technical description and single-center experience. (23rd July 2022) - Cappuzzo, J; Monteiro, A; Waqas, M; Baig, A; Popoola, D; Almayman, F; Khawar, W; Farkash, Z; Siddiqui, A; Levy, E; Snyder, K
Abstract : Background: The use of modern transfemoral balloon guide catheters (BGC) for flow reversal during carotid artery stenting (CAS) is scarcely described in literature but represents a promising and efficient technique for embolic protection. We describe the transfemoral flow-reversal procedure using the Walrus BGC and report our experience, aiming to evaluate the efficacy and safety of this novel technique. Methods: We performed a retrospective analysis of patients ≥ 18-year-old who underwent elective CAS with the use of flow-reversal through the Walrus BGC. Patients' characteristics, procedural details and clinical follow-up were evaluated. Results: One-hundred and ten patients were included. Mean age was 69.1 years ± SD 9.6 and 30 (27.3%) were female. Most common comorbidities were hyperlipidemia (81.8%) and hypertension (73.6%). 54 (49.1%) patients were symptomatic. 102 (92.7%) patients had stenosis ≥ 70%. Contralateral stenosis ≥ 50% was present in 54 (49.1%) patients. Distal filters were used in 91 (82.7%) cases. Angioplasty was performed in 86 (78.2%) patients. Stenting was successful in 100% of cases. There were no periprocedural TIA or stroke. Stroke or TIA and mortality were both observed in only two (1.8%) patients during 30-days follow-up. Conclusions: In our institution's experience, this technique was safe, feasible and efficient, with 100% technical success and no periprocedural thromboembolic complications. More extensive studies are needed to establish the role of proximal protection with flow-reversal using modern BGCs. Disclosures: J. Cappuzzo: None. A. Monteiro: None. M. Waqas: None. A. Baig: None. D. Popoola: None. F. Almayman: None. W. Khawar: None. Z. Farkash: None. A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc., . 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical, . E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical. K. Snyder: 2; C; Boston Scientific, Canon Medical Systems USA, Inc., MicroVention, Medtronic, Stryker Neurovascular. Payment or honoraria for lectures, presentations, speakers' bureaus, manuscript writing, or educati. 4; C; Boston Scientific, Access Closure Inc, Niagara Gorge Medical.